2020
DOI: 10.1002/dev.22015
|View full text |Cite
|
Sign up to set email alerts
|

Integrated and diurnal indices of maternal pregnancy cortisol in relation to sex‐specific parasympathetic responsivity to stress in infants

Abstract: Maternal hypothalamic‐pituitary‐adrenal axis activity may prenatally program sex‐specific stress‐response pathways. We investigated associations between maternal cortisol during pregnancy and infant parasympathetic responsivity to stress among 204 mother–infant pairs. Cortisol indices included 3rd trimester hair cortisol, as well as diurnal slope and area under the curve, derived from saliva samples collected during pregnancy. Mother–infant dyads participated in the Repeated Still‐Face Paradigm (SFP‐R) at age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…GWG was added as a covariate in each analysis as it has previously been associated with diurnal cortisol patterns in pregnancy in this cohort (Aubuchon‐Endsley et al., 2014). Based on extant literature, additional infant covariates were considered for current study analyses, including head circumference at birth (Ramsay & Lewis, 1995) and biological sex (Cowell et al., 2021; Kortesluoma et al., 2021). Sensitivity analyses were conducted to test if infant feeding during the NNNS exam (yes or no) impacted the results on infant cortisol and whether maternal wake time impacted the results of maternal CAR.…”
Section: Methodsmentioning
confidence: 99%
“…GWG was added as a covariate in each analysis as it has previously been associated with diurnal cortisol patterns in pregnancy in this cohort (Aubuchon‐Endsley et al., 2014). Based on extant literature, additional infant covariates were considered for current study analyses, including head circumference at birth (Ramsay & Lewis, 1995) and biological sex (Cowell et al., 2021; Kortesluoma et al., 2021). Sensitivity analyses were conducted to test if infant feeding during the NNNS exam (yes or no) impacted the results on infant cortisol and whether maternal wake time impacted the results of maternal CAR.…”
Section: Methodsmentioning
confidence: 99%
“…Study participants provided five passive drool saliva samples at the following defined time windows across three days within a 1-week period during the 3rd trimester of pregnancy (mean ± standard deviation: 33.0 ± 3.6 weeks, range: 27-39 weeks): (1) upon awakening, (2) 45 minutes (range: 30-90 minutes) after awakening and before the consumption of caffeine or food, (3) 4 hours (range: 4-6.5 hours) after awakening, (4) 10 hours (range: 7.5-11.5 hours) after awakening, and (5) before sleep (>11.5 hours after awakening) (Cowell et al 2021). Samples were collected at home and stored in the participant's personal refrigerator until collection by study staff.…”
Section: Salivary Cortisolmentioning
confidence: 99%
“…To capture this rhythm, we calculated three features of the daily cortisol curve as previously described in detail (Cowell et al 2021). Briefly, we calculated cortisol awakening rise (CAR), which provides information on the immediate postawakening increase, as the difference in cortisol between the first and second time points.…”
Section: Salivary Cortisolmentioning
confidence: 99%
“…Second, a large literature has demonstrated that exposure to maternal psychological states (stress, depression, and anxiety) beginning in the prenatal period and throughout the first years of life has differential sex and/or gender effects on numerous child outcomes, including stress responsivity and mental health (Van den Bergh & Marcoen, 2004; Van den Bergh et al, 2008, 2020). Moreover, studies suggest that maternal psychological states may influence child PNS reactivity specifically in a sex‐dependent fashion, including in early life (Cowell et al, 2021; Foss et al, 2022; Tibu et al, 2014). Additionally, there is some evidence that maternal internalizing symptoms interact with child PNS functioning to predict sex‐specific trajectories of child internalizing symptoms in middle childhood (Wetter & El‐Sheikh, 2012).…”
Section: Introductionmentioning
confidence: 99%